(Z)-1-(2,4-Difluorophenyl)-2-(1H-1,2,4-triazol-1-yl)ethanone oxime - Yu, Guang-yan (International Union of Crystallography, 2011)
In the title compound, C(10)H(8)F(2)N(4)O, the dihedral angle between the rings is 65.4 (1)°. In the crystal, intermolecular O—H⋯N and C—H⋯F hydrogen bonds link the molecules in a stacked arrangement along the a and c axes, respectively.